Political Regimes and Stock Market Performance in Africa - Simplice Asongu; Jacinta C. Nwachukwu (African Governance and Development Institute (AGDI), 2016)
This paper assesses the effect of political institutions on stock market performance in 14 African countries for which stock market data is available for the period 1990-2010. The estimation technique used is a Two-Stage-Least Squares Instrumental Variable methodology. Political regime channels of democracy, polity and autocracy are instrumented with legal-origins, religious-legacies, income-levels and press-freedom qualities to account for stock market performance dynamics of capitalization, value traded, turnover and number of listed companies. The findings show that countries with democratic regimes enjoy higher levels of financial market development compared to their counterparts with autocratic inclinations. As a policy implication, the role of sound political institutions has important effects on both the degree of competition for public office and the quality of public offices that favour stock market development on the African continent.
Keywords: G10; G18; G28; P16; P43; 330; Financial Markets; Government Policy; Development